2017
DOI: 10.1007/s11010-017-3209-4
|View full text |Cite
|
Sign up to set email alerts
|

SOX2-mediated inhibition of miR-223 contributes to STIM1 activation in phenylephrine-induced hypertrophic cardiomyocytes

Abstract: Stromal interaction molecule 1 (STIM1) is the key molecule responsible for store-operated Ca entry (SOCE). Numerous studies have demonstrated that STIM1 levels appeared to be enhanced during cardiac hypertrophy. However, the mechanism underlining this process remains to be clarified. In this study, phenylephrine (PE) was employed to establish a model of hypertrophic neonatal rat cardiomyocytes (HNRCs) in vitro, and low expression of primary and mature miR-223 was detected in PE-induced HNRCs. Our results have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…miRNAs have been implicated in regulating SOCE in different tissues. STIM1 expression has been shown to be regulated by miR-195 in intestinal epithelial cells (miR-195) 21 ; miR-424 in vascular smooth muscle 31 ; miR-185 in colorectal cancer 10 , and miR-223 in cardiac hypertrophy 32 and glioblastomas 33 .…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been implicated in regulating SOCE in different tissues. STIM1 expression has been shown to be regulated by miR-195 in intestinal epithelial cells (miR-195) 21 ; miR-424 in vascular smooth muscle 31 ; miR-185 in colorectal cancer 10 , and miR-223 in cardiac hypertrophy 32 and glioblastomas 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Current researches have demonstrated that miR-223-3p has biphasic effects on heart failure through bidirectional regulation of cardiac hypertrophy and promotion of inflammatory response. Both in the rat model of cardiac hypertrophy induced by transverse aorta constriction and in hypertrophic cardiomyocyte models treated with different inducing reagents endothelin-1 or phenylephrine, the expression of miR-223-3p in myocardium and cardiomyocytes were downregulated (124,125). The mechanism underlying the phenylephrineinduced downregulation of miR-223-3p in cardiomyocytes was suppressing glycogen synthase kinase 3 β activity to reduce β-catenin degradation and increase its activation (125).…”
Section: Effect Of Mir-223-3p On Pathophysiological Processes In Hearmentioning
confidence: 99%
“…Both in the rat model of cardiac hypertrophy induced by transverse aorta constriction and in hypertrophic cardiomyocyte models treated with different inducing reagents endothelin-1 or phenylephrine, the expression of miR-223-3p in myocardium and cardiomyocytes were downregulated (124,125). The mechanism underlying the phenylephrineinduced downregulation of miR-223-3p in cardiomyocytes was suppressing glycogen synthase kinase 3 β activity to reduce β-catenin degradation and increase its activation (125). This modulation upregulated SRY-box transcription factor 2, which could promote cardiomyocytes proliferation and increase heart size, to inhibit the transcription of primary miR-223 (125,126).…”
Section: Effect Of Mir-223-3p On Pathophysiological Processes In Hearmentioning
confidence: 99%
See 2 more Smart Citations